THE EFFECT OF CORNELL NOTE TAKING METHOD ON STUDENTSâ€™ GRAMMAR LEARNING AT MAN 1 KENDARI - Dewi, Nur Ayuni Sari; Rohmana, Rohmana; Miliha, La (Journal of Teaching of English, 2020)
This study was intended to investigate the effect of Cornell note taking method on the 11th grade studentsâ€™ grammar learning at MAN 1 Kendari. The research question of thisstudy was â€œIs there any significant effect of Cornell note taking method instruction on studentsâ€™ grammar learning at class XI of MAN 1 Kendari?â€. The scope of the study revolved around the students in 11th grade of MAN 1 Kendari and Grammar courses.The samples of this study were from class XI IPS 2 as control class and XI IPS 3 as experimental class; there are 20 students from each class. This study was a quantitative study that employed two-group) posttest-only design with Cornell note taking method as independent variable and studentsâ€™ grammar learning as dependent variable.The datawas collected through a grammar test with 35 items of questions. The data of this study was analyzed by usingSPSS 16.0. The result showed that there was 2.80200 score difference between both classes with control class obtained 3.92 and experimental class achieved 6.72. The data obtained via Independent Sample T-test presented the p value was.000. Thus, because the p value indicated that Sig. < Î± (0.05), it showed that H0was rejected and H1was accepted. Moreover, the calculated effect size, r = 0.6, was categorized as large. Therefore, it could be concluded that Cornell note taking method had worked well and carried a large effect on improving studentsâ€™ grammar learning at class XI IPS 3 of MAN 1 Kendari.